Successful pregnancies after transvenous cardiac resynchronization therapy in a woman with congenitally corrected transposition of the great arteries - Sana Ouali (The Egyptian Heart Journal, 2017)
Congenitally corrected transposition of the great arteries is a rare heart defect that can be associated with systemic ventricular dysfunction and conduction disturbances. The use of cardiac resynchronization therapy in patients with congenital heart disease is not fully established, and achievement of successful pregnancies after implantation of transvenous, biventricular system has never been described, and which resulted in a significant clinical improvement. We describe a 33-year-old female with congenitally corrected transposition of the great arteries, who achieved six pregnancies and successful vaginal deliveries. The two last pregnancies were achieved after cardiac resynchronization therapy for systemic ventricular dysfunction and complete heart block. A congenital cardiac disease has been identified in only one offspring.